Social Support and Psychological Distress of Women in Saudi Arabia: A Nationwide Cross-Sectional Study - Khulud K. Alharbi; Tassnym H. Sinky; Muath Aldomini; Mohamed O. Nour (Hindawi Limited, 2024)
Background. Social support is an important determinant of the psychological health of women. Aim. To examine social support and its association with psychological distress among women in Saudi Arabia. Materials and Methods. Data were gathered between February and July 2023, using a cross-sectional, anonymous, online survey of women in Saudi Arabia above the age of 18 (n = 414). The multidimensional scale of perceived social support was utilized to gauge social support. The brief symptom rating scale, a 5-item measure, was used to measure psychological distress. Associations between social support and psychological distress were determined using linear regression considering potential covariates. Results. Results show high levels of psychological distress, with 38.1% of respondents scoring moderate to severe levels of psychological distress. The most commonly reported symptoms of distress were "feeling tense or high-strung" and "feeling easily annoyed or irritated," with 39.4% and 34.5%, respectively, of respondents experiencing these symptoms moderately to extremely. Moderately high levels of social support were reported, with 77.1% of participants agreeing or strongly agreeing with the "my family really tries to help me" statement. Family/interpersonal relationships, however, were simultaneously the most commonly reported stressor over the past 3 years (59.4%). Unadjusted and adjusted analyses show social support was negatively correlated with psychological distress (β = −0.284, p <0.001; adjusted β = −0.145, p = 0.042), indicating higher levels of social support were correlated with reduced psychological distress. Conclusions. Findings indicate moderate-to-high levels of psychological distress as well as social support and an inverse association between them. This information can be used to inform intervention development. To better understand these domains as they relate to psychological distress, future research is warranted.